The formation of all-cis-(multi)fluorinated piperidines by a dearomatization-hydrogenation process - Nairoukh, Zackaria (Nat Chem, 2019)
Piperidines and fluorine-substituents are both independently indispensable components in pharmaceuticals, agrochemicals and materials. Logically, the incorporation of fluorine atoms into piperidine scaffolds is therefore an area of tremendous potential. However, synthetic approaches towards the formation of these architectures are often impractical. The diastereoselective synthesis of substituted monofluorinated piperidines often requires substrates with pre-defined stereochemistry. That of multifluorinated piperidines is even more challenging, and often needs to be carried out in multistep syntheses. In this report, we describe a straightforward process for the one-pot rhodium-catalyzed dearomatization–hydrogenation (DAH) of fluoropyridine precursors. This strategy enables the formation of a plethora of substituted all-cis-(multi)fluorinated piperidines in a highly diastereoselective fashion through pyridine dearomatization followed by complete saturation of the resulting intermediates by hydrogenation. Fluorinated piperidines with defined axial/equatorial orientation of fluorine-substituents were successfully applied in the preparation of commercial drugs analogues. Additionally, fluorinated PipPhos as well as fluorinated ionic liquids were obtained by this DAH process.